Decoding STAT3: a new frontier in understanding and treating hyperoxic lung injury - Li, Wulan; Liu, Qian; Xiong, Wenyan; Zhong, Xu; Tian, Lei (Frontiers in Immunology, 2025)
High-concentration oxygen (hyperoxia) therapy is critical for reducing mortality in hypoxemic emergencies, but it can also cause acute and chronic hyperoxic lung injury (HLI), such as diffuse alveolar damage, vascular endothelial injury, and bronchopulmonary dysplasia. Improving the safety of hyperoxia therapy has emerged as an urgent problem. The molecular mechanisms of HLI are not fully understood. Mono-therapy with antioxidant or anti-inflammatory agents has shown limited efficacy in mitigating lethal HLI, highlighting the need for multifaceted treatments. Signal transducer and activator of transcription 3 (STAT3) is involved in anti-inflammatory, anti-apoptotic, and antioxidant processes. Therefore, STAT3-targeted therapy may provide potential benefit in HLI treatment. Substantial evidence indicates that STAT3 is activated in lung cells following hyperoxia exposure and exerts both detrimental and protective effects. Given the increasing insights into STAT3’s role in HLI, a better understanding of the underlying mechanisms is necessary. This review explores the role of the STAT3 pathway in HLI across various cell types and disease models, and highlights recent developments in therapies targeting STAT3. We hope this summary can provide both advancements in understanding the STAT3 signaling pathway and evidence to support the development of novel therapeutic strategies targeting HLI.